1998
DOI: 10.1084/jem.187.9.1395
|View full text |Cite
|
Sign up to set email alerts
|

Direct Visualization of Antigen-specific CD8+T Cells during the Primary Immune Response to Epstein-Barr Virus In Vivo

Abstract: Primary infection with virus can stimulate a vigorous cytotoxic T cell response. The magnitude of the antigen-specific component versus the bystander component of a primary T cell response remains controversial. In this study, we have used tetrameric major histocompatibility complex–peptide complexes to directly visualize antigen-specific cluster of differentration (CD)8+ T cells during the primary immune response to Epstein-Barr virus (EBV) infection in humans. We show that massive expansion of activated, ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
546
3
5

Year Published

1998
1998
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 827 publications
(576 citation statements)
references
References 25 publications
20
546
3
5
Order By: Relevance
“…In persistent simian immunodeficiency virus infection in macaques, Kuroda et al 26 showed that epitope-specific T cells can account for as much as 10% of CD8 + T cells in the blood. Callan et al 27 have shown that between 7 and 44% of blood CD8 + T cells are EBV-specific in acute infection and the total number of CD8 + T cells is greatly increased, almost entirely by antigen-specific cells. MHC-II based tetramers were also prepared and widely used for the staining of CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In persistent simian immunodeficiency virus infection in macaques, Kuroda et al 26 showed that epitope-specific T cells can account for as much as 10% of CD8 + T cells in the blood. Callan et al 27 have shown that between 7 and 44% of blood CD8 + T cells are EBV-specific in acute infection and the total number of CD8 + T cells is greatly increased, almost entirely by antigen-specific cells. MHC-II based tetramers were also prepared and widely used for the staining of CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggested that only a minority of circulating melan-A-specific CTL in a minority of melanoma patients had a history of Ag exposure. However, CD45 isoforms are not in themselves adequate markers of memory/naivety, since memory cells can change expression patterns in vitro (18,19), and subpopulations of memory CTL specific for viral Ags can express converse CD45 isoforms in vivo (20,21).…”
mentioning
confidence: 99%
“…Following and monitoring spontaneous and postvaccinal immune responses remain elusive and limited to a handful of systems where TCRtransgenic mice are available. This paradigm has marginally benefited from the development of MHC tetramers that has been so successful for the detection of Ag-specific CD8 ϩ cytotoxic T cells (3,4). The reasons for the discrepancy between MHC class I and MHC class II tetramers are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The multimerization of MHC-peptide complexes answers partially this latter limitation by allowing an avidity effect and the staining of Ag-specific T cells (1,2). However, this method, largely used for the detection of cytotoxic CD8 ϩ T cells (3,4), has limitations. The first one of them is simply the geometry of display.…”
mentioning
confidence: 99%
See 1 more Smart Citation